THE ECONOMIC IMPORTANCE OF TRADITIONAL AND REGIONAL FOOD IN THE NORTHERN GREAT PLAIN REGIONTHE ECONOMIC IMPORTANCE OF TRADITIONAL AND REGIONAL FOOD IN THE NORTHERN GREAT PLAIN REGION - Halasi, Nóra (Applied Studies in Agribusiness and Commerce, 2025)
For a given region, competitiveness and sustainability play a vital role, as they are critical determinants of residents' quality of life and economic situation. The intensive implementation of rural development also offers opportunities for economic growth. Traditional and regional food products obviously give opportunities for the development of rural areas. Also, their production is significant for the local and Hungarian economies and society. Increasing the production of these food products and expanding and increasing their market outlets can contribute to maintaining the population in certain areas of the region and, among other things, protecting and preserving the tangible and intangible heritage of rural areas. Urban areas are also of particular importance for traditional and regional food: local events, such as themed festivals, and catering operators can also help to promote food products through a conscious, well-thought-out sales and marketing strategy.My research aims to characterize the economic position of traditional and regional food and products among local consumers in the Northern Great Plains region. During the survey, 1.349 people completed the questionnaire, and all of them gave valid responses. I focused on local specificities, gauging the opinions of residents in the region in relation to traditional food consumption in order to assess their willingness to pay more for traditional and regional food.